PENERAPAN MODEL TYLER PADA PENGEMBANGAN KURIKULUM BAHASA ARAB DI MTS JA-ALHAQ KOTA BENGKULU - Mamluatu Sholihah; Risda Aprilia; Fathi Hidayah (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2023)
Currently the curriculum is still developing. Curriculum changes aim to improve quality human resources. Curriculum development policy is one of the factors that influence the success or failure of the implementation of the curriculum development. The aim of this study is to identify the application of Tyler's model to the development of the Arabic language curriculum at Mts JÈƒ-alHaq. The research method uses a literature study or library research approach, in other words a qualitative research type. The results of this study can be analyzed that the application of the Tyler model to the development of the Arabic language curriculum at Mts JÈƒ-alHaq can be applied optimally and has a large impact, there are steps in the Tyler model that systematically make the Arabic language curriculum development process orderly. This can be seen from the emergence of new forms of learning that can be used in overcoming global challenges.